The Effect of Fins on Vortex Shedding - Jebodhsingh, Damon (My University, 2002)
An experimental study in air has been performed to determine what effect fins have on the flow over circular cylinders. The tubes under investigation included one bare tube and three segmented-finned tubes of different fin densities with the same root diameter as the bare tube. The tests were performed at two Reynolds numbers (2.61 x 104 and 4.98 x 104) and two downstream distances (2.5 & 5 diameters) and involved the use of hotwire anemometry. Measurements of mean and fluctuating velocities were taken across the wake as well as two-point fluctuating velocity correlations. It was discovered that the use of fins can result in significant differences. Fins cause larger mean velocity deficits in the wake profiles and significant shape differences in the total turbulence intensity profiles. Fins also increase the strength of vortex shedding, contrary to what would be expected, and increase the number of harmonic frequency peaks in the frequency spectra as three harmonic peaks were observed for the bare tube, while as many as ten were seen for the densest finned tube. Correlation length measurements, and thus radiated sound intensity, proved to be inconclusive. It was discovered that correlation length changed with angular rotation suggesting that this phenomenon needs to be investigated further before making any comparisons. Based on the differences seen with increased fin density, it is thought that there may be a critical fin density which causes fundamental changes in the cylinder wake. Also, during the course of this investigation, it was concluded that while the use of an effective diameter, De, proved adequate in collapsing the finned tube data, this approximation could be improved.
Keywords: fins; vortex shedding